2023
DOI: 10.3390/microorganisms11092266
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Aptamer Libraries in Fluorescence-Based Assays for Rikenella microfusus-Specific Gut Microbiome Analyses

Yiting Zhang,
Hu Xing,
Grigory Bolotnikov
et al.

Abstract: Rikenella microfusus is an essential intestinal probiotic with great potential. The latest research shows that imbalance in the intestinal flora are related to the occurrence of various diseases, such as intestinal diseases, immune diseases, and metabolic diseases. Rikenella may be a target or biomarker for some diseases, providing a new possibility for preventing and treating these diseases by monitoring and optimizing the abundance of Rikenella in the intestine. However, the current monitoring methods have d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…With the finding that polyclonal aptamer libraries originating directly from SELEX processes may outperform the individual aptamers [ 52 ] selected from these libraries, we introduced such enriched or “polyclonal” aptamer libraries as valuable tools for the fluorescent labeling of target structures and thus the specific quantification of a series of microbial symbionts and pathobionts [ 52 , 53 , 54 , 55 , 56 , 57 ]. Moreover, the functionality of this concept was further demonstrated with different tissues of plant roots [ 58 ] and by using specific enriched libraries for the construction of electronic gFET-based biosensors to measure pre-diabetes-related biomarkers [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the finding that polyclonal aptamer libraries originating directly from SELEX processes may outperform the individual aptamers [ 52 ] selected from these libraries, we introduced such enriched or “polyclonal” aptamer libraries as valuable tools for the fluorescent labeling of target structures and thus the specific quantification of a series of microbial symbionts and pathobionts [ 52 , 53 , 54 , 55 , 56 , 57 ]. Moreover, the functionality of this concept was further demonstrated with different tissues of plant roots [ 58 ] and by using specific enriched libraries for the construction of electronic gFET-based biosensors to measure pre-diabetes-related biomarkers [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that the relative abundance of Rikenella microfusus, Muribaculum intestinale, and Escherichia coli in the gut microbiota of red deer was significantly higher during SF than during NSF (Table S2). R. microfusus is an essential intestinal probiotic with great potential [72]. In previous studies in the cervids, it was found that Escherichia coli, Yersinia enterolitica, Y. ruckerii, Aeromonas sobria, Enterococcus faecium, Staphylococcus aureus, and Lysteria monocytogenes are potential pathogenic bacteria [23,73].…”
Section: Presumptionmentioning
confidence: 99%
“…Since the complex components on the cell surface may bias the library towards highly expressed epitopes, several combinatorial strategies have been reported such as precision-SELEX [ 30 ] or cross-over SELEX [ 31 ]. Recently, both SELEX and Cell-SELEX have been implemented to generate the possible aptamers for different pathogens and their subspecies, such as Escherichia coli [ 32 ], Staphylococcus aureus [ 33 ], Bacillus cereus [ 34 ], Streptococcus agalactiae [ 35 ], Rikinella microfusus [ 36 ], and many other medical and food-born pathogenic bacteria [ 37 , 38 ], to utilize them in biosensing or purification applications.…”
Section: Introductionmentioning
confidence: 99%